2007
DOI: 10.1038/ng.2007.41
|View full text |Cite
|
Sign up to set email alerts
|

Common genetic variants at the CRAC1 (HMPS) locus on chromosome 15q13.3 influence colorectal cancer risk

Abstract: We mapped a high-penetrance gene (CRAC1; also known as HMPS) associated with colorectal cancer (CRC) in the Ashkenazi population to a 0.6-Mb region on chromosome 15 containing SCG5 (also known as SGNE1), GREM1 and FMN1. We hypothesized that the CRAC1 locus harbored low-penetrance variants that increased CRC risk in the general population. In a large series of colorectal cancer cases and controls, SNPs near GREM1 and SCG5 were strongly associated with increased CRC risk (for rs4779584, P = 4.44 x 10(-14)).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
151
2
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 269 publications
(157 citation statements)
references
References 14 publications
3
151
2
1
Order By: Relevance
“…Three GWA studies of CRC have so far been reported and 10 independent loci shown conclusively to be associated with CRC risk: 8q24.21, 11q23, 18q21.1 (SMAD7), 8q23.1 (EIF3H), 15q (GREM1), 19q13.1 (RHPN2), 20q12.3, 14q22.2 (BMP4), 16q22.1 (CDH1) and 10p14 (Tomlinson et al, 2005Broderick et al, 2007;Zanke et al, 2007;Houlston et al, 2008;Jaeger et al, 2008;Tenesa et al, 2008). Risks associated with each of the common variants at each of these loci are modest (ORs 1.1 -1.3; Table 2) and there is little evidence of interactive effects.…”
Section: Characteristics Of Low-penetrance Variantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three GWA studies of CRC have so far been reported and 10 independent loci shown conclusively to be associated with CRC risk: 8q24.21, 11q23, 18q21.1 (SMAD7), 8q23.1 (EIF3H), 15q (GREM1), 19q13.1 (RHPN2), 20q12.3, 14q22.2 (BMP4), 16q22.1 (CDH1) and 10p14 (Tomlinson et al, 2005Broderick et al, 2007;Zanke et al, 2007;Houlston et al, 2008;Jaeger et al, 2008;Tenesa et al, 2008). Risks associated with each of the common variants at each of these loci are modest (ORs 1.1 -1.3; Table 2) and there is little evidence of interactive effects.…”
Section: Characteristics Of Low-penetrance Variantsmentioning
confidence: 99%
“…This assertion has recently been vindicated by genome-wide association (GWA) studies, which have provided robust evidence for several common low-risk variants influencing CRC risk (Tomlinson et al, 2005Broderick et al, 2007;Zanke et al, 2007;Houlston et al, 2008;Jaeger et al, 2008;Tenesa et al, 2008). Although the risk of CRC associated with each of these common variants is individually modest, they make a significant contribution to the overall disease burden by virtue of their high frequencies in the population.…”
Section: Introductionmentioning
confidence: 99%
“…Grem2 mRNA expression was significantly repressed in both Apc Min/þ and AOM-induced colon tumors, although we did not observe significant changes in Fmn2 expression. A recent GWAS identified common genetic variants at CRAC1 (HMPS) locus on human chromosome 15q13.3 that confers colorectal cancer risk in the Ashkenazi population (9). The CRAC1 locus was initially …”
Section: Discussionmentioning
confidence: 99%
“…Direct evidence for common variants for colorectal cancer is highlighted by recent genome-wide association studies (GWAS). These GWAS on colorectal cancer have identified 10 independent loci that confer risk of colorectal cancer, including those on chromosomes 8q24.21, 11q23, 18q21.1, 8q23.1 15q, 19q13.1, 20q12.3, 14q22.2, 16q22.1, and 10p14 (4)(5)(6)(7)(8)(9)(10). However, risk associated with these common variants is modest and only a small proportion of colorectal cancer risk can be explained by currently identified loci.…”
Section: Introductionmentioning
confidence: 99%
“…Much of the heritable risk of CRC is now thought to be the consequence of the co-inheritance of multiple low-risk variants. Such an assertion is supported by recent genome-wide association studies (GWASs) of CRC Tomlinson et al, 2007Tomlinson et al, , 2008Zanke et al, 2007;Houlston et al, 2008Houlston et al, , 2010Jaeger et al, 2008;Tenesa et al, 2008).…”
Section: Introductionmentioning
confidence: 54%